2005
DOI: 10.1016/j.molcel.2005.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Requirement for Both Recruitment and Postrecruitment Steps in Transcription Initiation

Abstract: Mediator complexes are required for activators to stimulate Pol II preinitiation complex assembly on an associated promoter. We show here that for the mouse Egr1 gene, controlled largely by MAP kinase phosphorylation of the ELK1 transcription factor, the MED23 Mediator subunit that interacts with phospho-ELK1 is also required to stimulate Pol II initiation at a step subsequent to preinitiation complex assembly. In Med23-/- cells, histone acetylation, methylation, and chromatin remodeling complex association at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
186
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(215 citation statements)
references
References 59 publications
29
186
0
Order By: Relevance
“…The ChIP protocol was performed as described previously [42]. Quantification of all ChIP sample was done by quantitative PCR (qPCR) using the TaKaRa SYBR Premix Ex Taq kit and a ABI 7500 fast.…”
Section: Chip Assaysmentioning
confidence: 99%
“…The ChIP protocol was performed as described previously [42]. Quantification of all ChIP sample was done by quantitative PCR (qPCR) using the TaKaRa SYBR Premix Ex Taq kit and a ABI 7500 fast.…”
Section: Chip Assaysmentioning
confidence: 99%
“…In the past few years, it has become evident that the so-called 'general transcription machinery' is in fact a huge repository of regulatory diversity. We now know that subunits of quasi-universal coregulators, such as TFIID or Mediator, play promoter-, signaling-and cell type-specific functions in gene expression (Chen et al, 1994;Albright and Tjian, 2000;Lemon et al, 2001;Brunkhorst et al, 2004;Mo et al, 2004;van de Peppel et al, 2005;Wang et al, 2005;Zhang et al, 2005;Loncle et al, 2007). In a revised model of transcriptional regulation control, specificity is not only provided by sequence-specific DNA-binding proteins, but also by non-DNA-binding coregulators once thought to be 'generic'.…”
Section: Lessons From Genome-wide Studiesmentioning
confidence: 99%
“…Given that Med23 is one of the tail modules of the mediator complex that controls a distinct gene expression pattern, our data suggest that Med23 may function as a key regulator of transcription that contributes to controlling T-cell activation to maintain T-cell homeostasis and self-tolerance. Med23 is known to mediate serum mitogen-induced IEGs expression, especially that of the EGR family genes 25,26 . Our gene expression analysis by microarray before or after TCR stimulation revealed that Med23-deficient T cells had reduced expression of Egr1 and Egr2, and these results were confirmed by real-time PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mediator complex seems to be universally required for the transcription of all genes, specific subunits are dedicated to the regulation of distinct expression programmes by interactions with relevant genespecific transcriptional activators 22 . Recently, the mediator subunit Med23 (also known as Sur2) has attracted attention because it regulates the mitogen-activated protein kinase signalling pathway 24,25 . Med23 mediates the immediate early gene (IEG) response to serum mitogens, which is required for mediator recruitment to a small subset of genes that are predominantly controlled by the mitogen-activated protein kinase signalling pathway 24,25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation